Attitudes of SMEs towards HRM in the most important business sectors in the V4 countries - Jaroslav Belas; Juraj Cug; Veronika Svatosova; Justas Streimikis (Serbian Journal of Management)
The main objective of the research study was to formulate the attitudes of SMEs that appropriately characterize the field of HRM. In a second step, these attitudes were compared in the three most important business sectors in the V4 countries. Data collection was carried out by the external agency MNFORCE using the "Computer Assisted Web Interviewing" in June 2022. The sample of 995 respondents consisted of SMEs belonging to the three most important sectors according to the number of respondents in each V4 country. The statistical hypotheses were tested using descriptive statistics and Z-scores at a significance level of α = 5%. According to our findings, SMEs in the V4 countries consider people in the firm as the most important asset, and statistically significant differences were found within the sample set. SMEs confirmed that they consider HRM as the most important area of corporate management. The empirical research showed the existence of statistically significant differences between the assessed sectors. In view of the previous results, the approach to staff performance appraisal and motivation can be considered appropriate. No statistically significant differences within the sample were found. The manufacturing sector demonstrated the best approach to each HRM claim in the V4 countries, followed by the trade and service sectors.